2017
DOI: 10.3389/fnins.2017.00629
|View full text |Cite
|
Sign up to set email alerts
|

Low Cost Electrode Assembly for EEG Recordings in Mice

Abstract: Wireless electroencephalography (EEG) of small animal subjects typically utilizes miniaturized EEG devices which require a robust recording and electrode assembly that remains in place while also being well-tolerated by the animal so as not to impair the ability of the animal to perform normal living activities or experimental tasks. We developed simple and fast electrode assembly and method of electrode implantation using electrode wires and wire-wrap technology that provides both higher survival and success … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…While these devices offer the benefits of wireless stimulation and flexible probes, which are ideal for experiments with freely moving animals and chronic implantation, respectively, they have complex designs which cannot be manufactured quickly and cheaply for high turnover experiments. Vogler et al (2017) effectively argue the benefits of simple, low cost devices for neural implantation and demonstrate how this design philosophy can be applied to EEG recordings. Furthermore, many of the stimulation devices described in literature are designed for rats, making them too large to properly function when used with mice.…”
Section: Introductionmentioning
confidence: 99%
“…While these devices offer the benefits of wireless stimulation and flexible probes, which are ideal for experiments with freely moving animals and chronic implantation, respectively, they have complex designs which cannot be manufactured quickly and cheaply for high turnover experiments. Vogler et al (2017) effectively argue the benefits of simple, low cost devices for neural implantation and demonstrate how this design philosophy can be applied to EEG recordings. Furthermore, many of the stimulation devices described in literature are designed for rats, making them too large to properly function when used with mice.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Spike Gadgets offers headcaps with a 32-channel capacity. (3) For other EEG systems, refer to Pinnell et al (2015 , 2016 ), Zayachkivsky et al (2015) , Vogler et al (2017) , Kent et al (2018) , Crouch et al (2019) , Medlej et al (2019) , Buenrostro-Jáuregui et al (2020) . A recent study conducted by Crouch et al (2019) demonstrated the utility of combined EEG and behavioral assessments in phenotyping mouse models of AD.…”
Section: Resultsmentioning
confidence: 99%
“…EEG activity was recorded in 2-month-old freely moving mice using a Neurologger recording device (TSE Systems) and processed with Spike2 v8.07 (Cambridge Electronic Design) analysis software. Surgeries were performed as previously described in Vogler et al (45). Briefly, mice were anesthetized with 3% isoflurane, the scalp removed, then 0.255 mm diameter electrodes were implanted 1 mm deep into 0.26 mm holes drilled into the skull and fastened with cyanoacrylate glue.…”
Section: Eeg Detection Of Epileptiform Activitymentioning
confidence: 99%